İbrahim en-Nazzâm'a göre insanın doğası ve zihinsel eylemleri - Bilici, Bilal (My University, 2022)
Tarih boyunca insan ve insana dair birçok problem araştırmanın konusu haline getirilmiş ve bu doğrultuda her dönemde insanın doğası yeniden anlamlandırılmaya çalışılmıştır. Bütünsel olarak insanı ele alarak onu düşüncenin nesnesi haline getiren ve böylece insana ait bedensel ya da zihinsel özelliklerin mahiyetini açıklamayı hedefleyen her girişim, bizlere insan hakkında önemli bilgiler sunmaktadır. Erken dönem kelamcıları da kendilerine böyle bir ilkeyi amaç edinip insanın doğasını, nasıl bir varlığa sahip olduğunu, onu diğer canlılardan ayıran niteliğin ne olduğunu ve onun bilişsel özelliklerini tüm netliğiyle ortaya koymaya çalışmışlardır. Bunu yaparken de sahip oldukları varlık anlayışlarından yararlanmışlardır. Çünkü insan da fiziksel ve zihinsel tüm özellikleriyle varlıklar kümesinin bir elemanı olarak değerlendirilmiştir. Nitekim bu konuda ortaya konan görüşlerin bazısı insanı, yalnızca bedensel ve maddî özelliklerini dikkate alarak tanımlamaya çalışırken bazıları ise onun zihinsel eylemlerini de göz önünde bulundurarak insanı soyut bir biçimde ele almıştır. Tezimizde erken dönem kelamcılarından biri olarak İbrahim en-Nazzâm’ın insanın doğası ve zihinsel durumları hakkında dile getirmiş olduğu düşünceleri kendi öğretisi içerisinde incelemeye çalışılacaktır. Dolayısıyla bu tezde, Nazzâm’ın insan tanımı ve ruh hakkındaki görüşleri incelenmekle birlikte onun duyumsama ve idrakin nasıl gerçekleştiği, insanın zihinsel durumlarının kaynağı sorunu, düşüncenin merkezi, ruh-beden ikilemi vb. birçok konu hakkındaki düşünceleri ortaya koyulmaya çalışılacaktır. Bu amaçla araştırmamıza ilk olarak erken dönem kelamında ileri sürülen insan tanımlarını incelemekle başlayacağız. Erken dönem kelamcıların insanı hangi açıdan ele aldıklarını açıklamaya çalışacağız. Daha sonra Nazzâm’ın probleme yaklaşımını inceleyerek onun insana dair düşüncelerini aktarmayı hedeflemekteyiz. İkinci bölümde ise Nazzâm’ın insanın doğasına dair görüşlerinden hareketle onun insanın bilişsel özellikleri hakkında bizlere neler sunduğunu göstermeye çalışacağız.

Throughout history, human and many problems related to humans have been made the subject of research and in this direction, the nature of human has been tried to be re-interpreted in every period. Every attempt that takes the human being holistically and makes him an object of thought, and thus aims to explain the nature of human physical or mental characteristics, provides us with important information about human beings. The early theologians set such a principle as their aim and tried to reveal the nature of man, what kind of existence he has, what distinguishes him from other living things, and his cognitive features with all clarity. While doing this, they benefited from their understanding of existence. Because human, with all his physical and mental features, has been evaluated as an element of the schema of existence. As a matter of fact, some of the views put forward on this subject try to define human beings by considering only their bodily and material characteristics, while others consider human beings in an abstract way, taking into account his mental actions.In our thesis, we will try to analyze the views expressed by İbrahim en-Nazzam, as one of the early theologians, about the nature and mental states of human beings, by interpreting them in his own teaching. Also in this thesis; Nazzam's definition of human, his views on the soul, the source of human life, how perception and perception occur, the source of human mental states, the center of thought, the soul-body dilemma etc. It will be tried to reveal how Nazzam gave answers to many issues. In our thesis, we will try to analyze the views expressed by İbrahim en-Nazzam, as one of the early theologians, about the nature and mental states of human beings, by interpreting them in his own teaching. Also in this thesis; Nazzam's definition of human, his views on the soul, the source of human life, how perception and perception occur, the source of human mental states, the center of thought, the soul-body dilemma etc. It will be tried to reveal how Nazzam gave answers to many issues. For this purpose, we will start our research by examining the definitions of human being put forward in the early period. We will try to explain from which perspective the early theologians approached the human being. Then, by examining Nazzam's approach to the problem, we aim to convey the dimensions of the effects of his thoughts on human beings on the history of kalam. In the second part, we will try to show what Nazzam offers us about the cognitive characteristics of human, starting from his views on the nature of human being. The results we have reached regarding the human nature in the early period theology will serve us to comprehend the nature of the human being today as it was in the past.
Keywords: Beden; Biliş Nazzâm; Body; Cognition; Human; Islam; İdrak; İnsan; İslam; Mind; Nazzâm; Perception; Zihin